Omkring Grundtvigs historieskrivning - status og fremtidsperspektiver - Aarnes, Sigurd Aa (Grundtvig-studier, 1965)
Grundtvig3s Historical Writings - Status and Perspectives By Sigurd Aa. Aarnes. For long periods of his life Grundtvig was occupied with the research and representation af history. If as a historian he has, nevertheless, been almost forgotten, it is because his type and aim make him cut across the main trend of nineteenth century positivistic research and historical criticism. Grundtvig was not a historian in the modern professional sense of the word but a narrator and philosopher. He does not aim at establishing historical facts, “wie es eigentlich gewesen” (Leopold von Ranke). He is more concerned with the question how to make history serve the cause of national and religious revival for which he is fighting. As a result of this Grundtvig’s historical writings are of minor interest as such (i.e. as historical writings). We study them today because they are sources of the history of ideas, interesting not by the world history they impart but by what they imply about Grundtvig himself and his age. In the last part of the article the author mentions some objects of research within the field in question. Grundtvig” s chief work of history, the monumental Haandbog i Verdens-Historien (1833-44), has not yet been sufficiently examined. Nor has special attention been paid to the influence of Grundtvig’s historical works on contemporary writers and on the teaching of history in the Folk Highschool. For any study of Grundtvig as a critic of the age his historical writings are of the first importance.